Concussion among soccer players in the 2017 Brazilian championship – the gap between protocol and medical practice - Cármine Porcelli Salvarani; Lucas Ribeiro de Medeiros; Fernando Henrique Sapatero; Diego Ciotta de Castro; Vinícius Simon Tomazini; Leonardo Henrique Micheletti Sotocorno; Paulo Sérgio Teixeira da Costa; Bruno Bueno Pimenta; Diego Almeida de Oliveira; Eduardo Almeida Dias; Eduardo Vinícius Colman da Silva (Concussion)
Background: The present study aims to report traumatic brain injury (TBI) among soccer players in the 2017 Brazilian Soccer Championship and discuss the protocols for concussion evaluation. Materia...